Effect of Pruning and Nutritional Levels on Growth of.Jatropha (Jatropha curcas) under Rainfed Conditions - Patil, S.J.; Mutanal, S.M.; Shahapurmath, G.B.; Mannikeri, I.M. (Indian Journal of Agroforestry, 2020)
Two field experiments were conducted to standardize the pruning and nutritional levels on growth and yield of Jatropha under rainfed conditions at Main Agricultural Research Station, Dharwad and Agricultural Research Station, Prabhunagar (Dharwad) during 2004 and 2003 respectively on medium black soils. Jatropha seedlings/seeds were planted/dibbled at 3x2 m apart. Both the experiments were laid out in factorial randomized block design with three replications. At Dharwad, the experiment consisted of two factors viz,. Pruning levels (1m, 1.5m and no pruning) and sulphur levels (20, 40, 60, kg/ha). Collar diameter, number of branches and seed yield of Jatropha were significantly higher in 1 m pruned height as compared to no pruning. Seed yield of Jatropha was higher with the application of sulphur @ 60kg/ha as compared to 20kg/ha. Whereas, at Prabhunagar, the experiment consisted of two factors viz,. Fertilizers levels (40:40:40, 60:60:60, 80:80:80 N:P:K g/plant) and Pruning levels (1m, 1.5,m 2m and no pruning). Application of 80:80:80 N:P:K g/plant had recorded significantly higher number of branches, collar diameter and seed yield as compared to 40:40:40 N:P:K g/plant. Number of branches and collar diameter of Jatropha were Â significantly higher in 1m pruning as compared to other pruning levels.